Experiences of unemployment and well-being after job loss during economic recession: Results of a qualitative study in east central Sweden - Anne-Sofie Hiswåls; Anneli Marttila; Emelie Mälstam; Gloria Macassa (SAGE Publishing, 2017)
Introduction: Several studies have revealed an association between unemployment and ill health, and shown that unemployment can affect people differently. This study aimed to provide an understanding of the experiences of unemployment and perceptions of wellbeing among persons who involuntary lost their work during the recent economic recession in Gävle Municipality. Methods: Sixteen unemployed men and women aged 28-62 were interviewed face-to-face. A purposeful sampling strategy was used in order to suit the research question and to increase the variation among informants. The interview texts were analysed using thematic analysis. Results: Six different themes emerged from the accounts: The respondents perceived work as the basis for belonging, and loss of work affected their social life and consumption patterns due to changes in their financial situation. They also expressed feelings of isolation, loss of self-esteem, and feelings of hopelessness, which affected their physical well-being. Longer duration of unemployment increased the respondents' negative emotions. The respondents reported activities, structure, and affiliation in other contexts as part of their coping strategy against poor mental health. Conclusions: After job loss, the respondents experienced feelings of loss of dignity and belonging as a human being. They also felt worry, insecurity, and stress due to their changed financial situation, which in turn led to isolation and loss of self-esteem. Social support and having other activities gave the respondents structure and meaning.